2014
DOI: 10.1140/epjb/e2014-50221-3
|View full text |Cite
|
Sign up to set email alerts
|

Anderson localisation on the Falicov-Kimball model with Coulomb disorder

Abstract: The role of Coulomb disorder is analysed in the Anderson-Falicov-Kimball model. Phase diagrams of correlated and disordered electron systems are calculated within dynamical mean-field theory applied to the Bethe lattice, in which metal-insulator transitions led by structural and Coulomb disorders and correlation can be identified. Metallic, Mott insulator, and Anderson insulator phases, as well as the crossover between them are studied in this perspective. We show that Coulomb disorder has a relevant role in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In strong interaction regime, the metallic states are not available as the system is always gapped regardless of disorder strength [18,21]. It is interesting to note that new AI regions that appear in the absence of Anderson disorder were found in the Bose-Hubbard model [10,11] as well as in the Anderson-Falicov-Kimball with random on-site interactions [30], now we for the first time find it in the AHM with Coulomb disorder.…”
Section: Resultsmentioning
confidence: 58%
“…In strong interaction regime, the metallic states are not available as the system is always gapped regardless of disorder strength [18,21]. It is interesting to note that new AI regions that appear in the absence of Anderson disorder were found in the Bose-Hubbard model [10,11] as well as in the Anderson-Falicov-Kimball with random on-site interactions [30], now we for the first time find it in the AHM with Coulomb disorder.…”
Section: Resultsmentioning
confidence: 58%
“…It is worth to emphasize that nonhomogeneous charge phases play an important role in studies of various phenomena modeled by the FKM including crystallization [77][78][79], metal-insulator and valence transitions [80][81][82][83][84][85][86][87][88][89], localization [86,[90][91][92][93], distribution of heavy and light cold atoms in optical lattices [70,[94][95][96][97] or the studies of non-local correlations [98][99][100][101]. They should be also considered when addressing different nonequilibrium phenomena [102][103][104][105][106][107][108][109][110] and any type of transport [73,93,[111][112][113][114][115] while dealing with a system outside the PHS point, e.g., a doped system.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the TDOS vanishes continuously as the strength of the disorder increases toward the critical point and it can be used as an order for the Anderson localization transition. This scheme uses only one-particle quantities and can be incorporated into the DMFT for disordered electrons in presence of Coulomb correlations [8][9][10]. Recently, the metal-insulator phase diagram in the half-filled HM with a box disorder has been investigated within the TMT -DMFT with different standard numerical impurity solvers, such as the numerical renormalization group (NRG) method [11], the four boson technique (SB4) [12].…”
Section: Introductionmentioning
confidence: 99%